2022
DOI: 10.36552/pjns.v26i2.690
|View full text |Cite
|
Sign up to set email alerts
|

Results of Lumbar Transpedicular Fixation for Spondycolisthesis, in Terms of Back Pain Relief

Abstract: Objective:  The goal of this study was to see how transpedicular fixation for degenerative spondylolisthesis affected lumbago. Methodology:  A retrospective observational study was conducted at the Department of Neurosurgery in Hayatabad Medical Complex, Peshawar between May 2018 and February 2020. Degenerative spondylolisthesis was diagnosed using static and dynamic spinal X-rays. The research excluded the patients with grade 5 spondylolisthesis, congenital anomalies, or prior spinal surgery. The visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
(15 reference statements)
2
1
0
Order By: Relevance
“…We found that 90% of the patients had signs of radiological fusion at 6month followup. Similar findings were reported by Ishaq et al 21 and Amir et al 22 The greater degree of fusion is associated with improvement in back pain symptoms and favorable outcomes overall. As we did not perform any interbody fusion, these findings also support the argument that transpedicular fixation alone without interbody fusion can have a higher grade of fusion rates.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We found that 90% of the patients had signs of radiological fusion at 6month followup. Similar findings were reported by Ishaq et al 21 and Amir et al 22 The greater degree of fusion is associated with improvement in back pain symptoms and favorable outcomes overall. As we did not perform any interbody fusion, these findings also support the argument that transpedicular fixation alone without interbody fusion can have a higher grade of fusion rates.…”
Section: Discussionsupporting
confidence: 87%
“…30 (50%) of the patients and L5-S1 was the most frequent level involved (40%) followed by L4-5 (38.3%). Similar findings were reported by Ishaq et al 21 and Amir et al, 22 however, Singha et al, 23 and Ewiss et al, 24 found L4-5 as the most common level involved (70% and 76% of cases respectively).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation